2011
DOI: 10.1088/0957-0233/22/3/035201
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the diagnostic information in the response patterns of a temperature-modulated tin oxide gas sensor

Abstract: The transient response patterns of a tin oxide chemoresistive gas sensor, temperature-modulated by the application of staircase voltage waveforms to its microheater, to five different volatile organic compounds were compared with respect to their target gas discriminating features. These patterns were divided into a number of segments, each corresponding to a temperature transition at the surface of the tin oxide pallet. The effectiveness of the gas discriminating information content of each segment was quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…In order to compare measured output and the output of a trained network, fitness criterion is computed for each segment [9]. Based on the results of fitness computations, the smallest and best model order for each five defined systems is selected.…”
Section: Modelling and Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to compare measured output and the output of a trained network, fitness criterion is computed for each segment [9]. Based on the results of fitness computations, the smallest and best model order for each five defined systems is selected.…”
Section: Modelling and Feature Extractionmentioning
confidence: 99%
“…Attempts have been made to create selectivity in a single sensor [8]. One of the techniques that's commonly used for creating the capability of selectivity in single sensors is the modulation of sensor temperature [9][10]. Various studies have shown that gas sensors with modulated working temperature yield more discriminant features.…”
Section: Introductionmentioning
confidence: 99%
“…MOS sensors under TM are believed to provide richer information and have better selectivity than those operated in the ordinary way [36], [37]. In the proposed system, we applied a staircase modulation voltage [36], [37] to three MOS sensors. Experiments with real breath samples show that sensor arrays with these TM sensors have higher accuracy.…”
Section: A Sensor Selectionmentioning
confidence: 99%
“…Metal-oxide thin film sensors have been widely used for gas sensing applications thanks to their sensitivity toward a large variety of gases [1]. Modulating the temperature of a micro-hotplate gas sensor allows increasing the sensitivity and/or selectivity toward various gases [2][3][4][5][6][7][8][9][10][11][12][13][14]. In some cases, the transient behavior of the sensing resistance, located just after a temperature change, is used to discriminate gases by comparing signal shapes [10,11].…”
Section: Introductionmentioning
confidence: 99%